2007
DOI: 10.1021/je700556p
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium System of LuCl3−CdCl2−HCl(7.47 %)−H2O at 298.15 K and Standard Molar Enthalpies of Formation of New Solid-Phase Compounds

Abstract: The equilibrium solubility of the quaternary system LuCl 3 -CdCl 2 -HCl-H 2 O was determined at 298.15 K, and the corresponding equilibrium diagram was constructed in this paper. The quaternary system is complicated with four equilibrium solid phases, CdCl 2 • H 2 O, Cd 3 LuCl 9 • 14H 2 O (3:1 type), CdLuCl 5 • 9H 2 O (1:1 type), and LuCl 3 • 6H 2 O, of which the new compounds Cd 3 LuCl 9 • 14H 2 O and CdLuCl 5 • 9H 2 O were found to be congruently soluble in the system. The two new compounds obtained were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…But for the quaternary systems TbCl 3 −CdCl 2 −HCl−H 2 O and DyCl 3 −CdCl 2 −HCl−H 2 O, there are only three equilibrium solid phases (CdCl 2 ·H 2 O, Cd 4 TbCl 11 ·14H 2 O, and TbCl 3 ·6H 2 O) and (CdCl 2 ·H 2 O, Cd 9 Dy 2 Cl 24 ·29H 2 O, and DyCl 3 ·6H 2 O). We re-examined the YCl 3 −CdCl 2 −HCl−H 2 O, ErCl 3 −CdCl 2 −HCl−H 2 O, and LuCl 3 −CdCl 2 −HCl−H 2 O systems and confirmed that the YCl 3 −CdCl 2 −HCl−H 2 O system is composed of four equilibrium solid phases: CdCl 2 ·H 2 O, Cd 4 YCl 11 ·13H 2 O, Cd 5 Y 2 Cl 16 ·26H 2 O, and YCl 3 ·6H 2 O, respectively. For the ErCl 3 −CdCl 2 −HCl−H 2 O system, four equilibrium solid phases (CdCl 2 ·H 2 O, Cd 9 Er 2 Cl 24 ·29H 2 O, CdEr 7 Cl 23 ·42H 2 O, and ErCl 3 ·6H 2 O) were observed.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…But for the quaternary systems TbCl 3 −CdCl 2 −HCl−H 2 O and DyCl 3 −CdCl 2 −HCl−H 2 O, there are only three equilibrium solid phases (CdCl 2 ·H 2 O, Cd 4 TbCl 11 ·14H 2 O, and TbCl 3 ·6H 2 O) and (CdCl 2 ·H 2 O, Cd 9 Dy 2 Cl 24 ·29H 2 O, and DyCl 3 ·6H 2 O). We re-examined the YCl 3 −CdCl 2 −HCl−H 2 O, ErCl 3 −CdCl 2 −HCl−H 2 O, and LuCl 3 −CdCl 2 −HCl−H 2 O systems and confirmed that the YCl 3 −CdCl 2 −HCl−H 2 O system is composed of four equilibrium solid phases: CdCl 2 ·H 2 O, Cd 4 YCl 11 ·13H 2 O, Cd 5 Y 2 Cl 16 ·26H 2 O, and YCl 3 ·6H 2 O, respectively. For the ErCl 3 −CdCl 2 −HCl−H 2 O system, four equilibrium solid phases (CdCl 2 ·H 2 O, Cd 9 Er 2 Cl 24 ·29H 2 O, CdEr 7 Cl 23 ·42H 2 O, and ErCl 3 ·6H 2 O) were observed.…”
Section: Introductionmentioning
confidence: 75%
“…Phase equilibria of quaternary systems of RECl 3 −CdCl 2 −HCl(∼8 %)−H 2 O (RE = La, Ce, Pr, Nd, Eu, Tb, Dy, Y, Er, Lu) at 298.15 K have been previously reported. It is highly valuable and important for us to understand the phase relations and interactions of RECl 3 and CdCl 2 in aqueous media. Li et al and Wang et al , reported the presence of four equilibrium solid−phase regions (CdCl 2 ·H 2 O, Cd 8 RECl 19 · n H 2 O, Cd 4 RECl 11 ·12H 2 O, and RECl 3 ·7H 2 O) (RE = La, Pr, n = 16, 20) in the LaCl 3 −CdCl 2 −HCl−H 2 O and CdCl 2 −PrCl 3 −HCl−H 2 O quaternary systems.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation